Graphic Interlude - Fergus Fields; Carol M. Highsmith; Walker Evans; Samuel J. Beckett; Thomas C. Roche; Alexander Gardner; John Collet (Angles)
This graphic interlude features a selection of photographs which can illustrate the topic of this issue: “Unstable states, mutable conditions”.